Factors associated with the quality of life of Brazilian adults and the elderly: a cross-sectional study (Research, Society and Development, 2022)
The objective of this study was to analyze the association between socioeconomic, demographic, lifestyle, health, nutrition and food insecurity factors and quality of life (QoL) in 295 Brazilian adults and the elderly residents in Natal-RN, using data from the Brazilian Usual Consumption Assessment – BRAZUCA survey. Multivariate analysis using Poisson Regression was using, to verify the association between the Qol, assessed by the WHOQOL-bref instrument, with the independent variables. Having age 40-59 years (PR=1.70; 95%CI 1.10-2.62) or age ≥ 60 years (PR=1.55; 95%CI 1.00-2.40); having non-white skin (PR=1.56; 95%CI 1.10-2.19); and being in mild food insecurity (PR=2.70; 95%CI 1.75-4.19) moderate (PR=3.19; 95%CI 2.03-5.00) or severe (PR=3.12; 95%CI 1.80-5.42) were associated with a higher probability of Perceived QoL regular, poor, or very poor. Satisfaction with regular, unsatisfactory, or very unsatisfactory health was associated with mild food insecurity (PR= 1.73; 95%CI 1.26-2.37), emotional disturbances (depression or anxiety) (PR=1.88; 95%CI 1.43-2.49) and being hypertensive (PR=1.39; 95%CI 1.05-1.84). The results suggest the need for public policies that fight inequality, hunger, and promote healthy lifestyles.